Hubungan Minat Baca dan Kecerdasan Interpersonal Siswa terhadap Hasil Belajar IPS Siswa Kelas IV MI Muhammadiyah Al-Manar Demak - Innayatun Nashihah; Nanang Nabhar Fakhri Auliya (JEID: Journal of Educational Integration and Development, 2022)
This study aims to obtain several findings, namely 1) there is a relationship between the variables of reading interest and interpersonal intelligence on learning outcomes in social studies subjects in grade IV. 2) there is an indirect effect of reading interest on social studies learning outcomes through interpersonal intelligence. The population in this study were 30 students, all of which were 30 students who were also the sample in this study. The data analysis technique uses path analysis with the help of the SPSS version 25 application as a tool for processing and research. The results showed that the variables of reading interest and interpersonal intelligence had an effect and were significant on the social studies learning outcomes variable in the odd semester of TP 2020/2021. The direct effect of reading interest and interpersonal intelligence on learning outcomes is 0.179 or 17.9% and the effect of mediation on reading interest on learning outcomes through interpersonal intelligence is 1.97 or 1.97%. Keywords: Reading Interest, Interpersonal Intelligence, and Social Studies Learning Outcomes